2022
DOI: 10.3174/ajnr.a7716
|View full text |Cite
|
Sign up to set email alerts
|

Viz.ai Implementation of Stroke Augmented Intelligence and Communications Platform to Improve Indicators and Outcomes for a Comprehensive Stroke Center and Network

Abstract: BACKGROUND AND PURPOSE: Comprehensive stroke centers continually strive to narrow neurointerventional time metrics. Although process improvements have been put in place to streamline workflows, complex pathways, disparate imaging locations, and fragmented communications all highlight the need for continued improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Prior studies have examined the effect of automated LVO detection on in-hospital quality metrics, as well as clinical outcomes. Several studies have found statistically significant reductions in DTG time and one study identified a reduction in hospital length of stay . These prior studies have been limited by several factors, which include small sample sizes, single-hospital data, and heterogenous populations that include both transfer patients as well as direct emergency department presentations.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have examined the effect of automated LVO detection on in-hospital quality metrics, as well as clinical outcomes. Several studies have found statistically significant reductions in DTG time and one study identified a reduction in hospital length of stay . These prior studies have been limited by several factors, which include small sample sizes, single-hospital data, and heterogenous populations that include both transfer patients as well as direct emergency department presentations.…”
Section: Discussionmentioning
confidence: 99%
“…When the application is accessed, real-time, dynamic, high-fidelity three-dimensional (3D) images can be viewed on the phone along with image rotation, allowing better visualization of vessel morphology (Figurelle et al., 2023). The cloud-based technology automates and provides the maximum-intensity projection of 3D images (Figure 2; Elijovich et al., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The platform provides HIPAA-compliant group communication messaging. Members can dialogue and exchange information on the same page (Figure 3; Figurelle et al., 2023; Morey et al., 2021). To be part of the messaging group, the application has to be toggled to “on-call,” resulting in case images received when on shift (Figurelle et al., 2023).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations